Overview, Management of the Infections in Psoriatic Patients Treated with Systemic Therapies: A lesson from the immunopathogenesis of psoriasis - Balato, Anna; Scala, Emanuele; Eyerich, Kilian; Brembilla, Nicolo Costantino; Chiricozzi, Andrea; Sabat, Robert; Ghoreschi, Kamran (Dermatology Practical & Conceptual, 2023)
Modern treatments continue to be developed, based on identifying targets within the innate and adaptive immune pathways associated with psoriasis. Whilst there is a sound biologic rationale for increased risk of infection following treatment with immunomodulators, the clinical evidence is confounded by these agents being used in patients affected with several comorbidities. In an era characterized by ever greater and growing risk of infections, it is necessary to always be updated on this risk. In this review, we will discuss recent updates in psoriasis immunopathogenesis as a rationale for systemic therapy, outline the risk of infections linked to the disease itself and systemic therapy as well, and provide an overview about the management of infections.